Analytical and numerical solutions in the context of Cosserat continuum as the basis for experiments on detection of couple-stress effects in materials - Korepanov, Valery Valer'evich; Kulesh, Mikhail Alexandrovich; Matveenko, Valery Pavlovich; Shardakov, Igor Nikolaevich (Computational Continuum Mechanics, 2009)
The analysis of analytical and numerical solutions to static problems obtained in the framework of the Cosserat continuum theory has been made for a special purpose to ascertain the effects due to couple-stress properties of materials. The appropriate macro-parameters have been identified and the measure of their response to couple-stress properties has been determined. A set of solutions, which are most informative from the view point of manifestation of couple-stress properties, has been found. These solutions have been used as a basis for development and realization of experiments on registration of couple-stress effects in the examined materials.
Keywords: Cosserat continuum; analytical and numerical solutions; experimental identification of parameters